Sesame Street. Silly storytime [videorecording (DVD)] - Clash, Kevin; Lehmann, Benjamin, 1967-; Berger, Lou; May, Ted (Sesame Street (Television program), 2011)
Includes beloved fairy tales Rapunzel; Sleeping Beauty; Jack and the Beanstalk; and Little Ride Robin Hood. Featuring four classic Kermit Newsflash segments. Preschooler will learn early literacy skills, problem solving, and exploring nature.